Ulysses/Galileo observations of type III radio bursts and associated in-situ electrons and Langmuir waves - Reiner,MJ; Anderson,KA; Roelof,E; Armstrong,T; Hospodarsky,GB; Fainberg,J; Stone,RG; Lanzerotti,L; Gurnett,DA; Phillips,JL; Forsyth,R (Space Science Reviews, 1995)
Both the Ulysses and Galileo spacecraft detected energetic electrons and Langmuir waves that were associated with a type III radio burst on 10 December 1990. At the time of these observations, these spacecraft were in the ecliptic plane and separated by 0.4 AU, with Galileo near the Earth at 1 AU and Ulysses at 1.36 AU. From the measured electron arrival times, the propagation path lengths of the electrons to both Ulysses and Galileo were estimated to be significantly longer than the length of the Parker spiral. These long path lengths are interpreted as due to draping of the interplanetary magnetic field lines around a CME. The onset times of the Langmuir waves at Ulysses and Galileo coincided with the estimated arrival time of the 9 keV and 14 keV electrons, respectively. © 1995 Kluwer Academic Publishers.